The challenges to democracy in Iraq : a case study of the Iraqi governing elite (2014-2020) - Mohammed, Shakar Ibrahim
The democratic process in Iraq is in crisis and strong challenges prevent the development of a genuine democratic system. These include but not limited to the current Muhasasa system, the diminishing protection of individual rights and personal liberty of the Iraqi people, the general insecurity of lives and property, the rise of ISIS and other militia groups, all owing to the waning capacity of the ruling elite to truly democratize the Iraqi politics. This dissertation examines and discusses the challenges of democracy in analysing the role of the Iraqi governing elite in the national democratization process. What is the role of the Iraqi governing elite in building democracy in Iraq? How has the Iraqi governing elite reacted during the political crisis of 2014-2020 in terms of their commitment to basic democratic principles? What is the extent of the Muhasasa system contributed to the stagnation of democracy in Iraq? Data were sourced from the Iraqi Constitution, personal interviews, dissertations, articles, books, and online newspapers. It finds that elite political formations have been an important and increasingly effective character Iraqi political process throughout the creation and development of Iraq as a country. It further revealed that several crises in Iraq from 2014 to 2020 which required reactions from the Iraqi governing elite, but instead they utilized and monopolized state resources, powers, and control of key political, national, popular, financial, and security institutions. This situation gave rise to extremist groups seizing control of significant parts of Iraqi territories and helped create several militias and military forces in Iraq. The Iraqi governing elite utilized these circumstances to boost their own positions and factional strength. The thesis recommends that the Iraqi government should provide equal opportunities for Iraqi citizens in governance and the rule of law to transcend sectionalism, and genuinely free and fair national elections should be held, supervised by the UN. Political militias must be gradually disbanded or at least prevented from direct interference in governance, and a more meritocratic system of appointment to state roles must be developed.